2014
DOI: 10.1016/j.lwt.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sequential fermentation with Torulaspora delbrueckii and Saccharomyces cerevisiae on wine quality

Abstract: Torulaspora delbrueckii is a non-Saccharomyces yeast with interesting metabolic and physiological properties of potential use in oenology. This work examines the fermentative behaviour of five strains of T. delbrueckii in sequential fermentations with Saccharomyces cerevisiae, analysing the formation of aromatic compounds, polyalcohols and pigments. The fermentative power of these five strains ranged between 7.6 and 9.0% v/v ethanol; the associated volatile acidity was 0.2-0.7 g/1 acetic acid. The production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
93
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 47 publications
16
93
6
1
Order By: Relevance
“…For these reasons, several studies have suggested the use of T. delbrueckii in combination with S. cerevisiae starter strains [2,21,22], with the clearly evident contributions of T. delbrueckii to the wine aroma leading to its recent commercialization. On the basis of these considerations, we evaluated the influence of selected strain Td92 T. delbrueckii in sequential fermentations with S. cerevisiae and Verdicchio grape juice, while also evaluating two S. cerevisiae starter strains and three vintages of grape juice.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, several studies have suggested the use of T. delbrueckii in combination with S. cerevisiae starter strains [2,21,22], with the clearly evident contributions of T. delbrueckii to the wine aroma leading to its recent commercialization. On the basis of these considerations, we evaluated the influence of selected strain Td92 T. delbrueckii in sequential fermentations with S. cerevisiae and Verdicchio grape juice, while also evaluating two S. cerevisiae starter strains and three vintages of grape juice.…”
Section: Discussionmentioning
confidence: 99%
“…delbrueckii produced the highest concentrations of 3-ethoxy propanol (Loira et al 2014) described as responsible of blackcurrant aroma in red wines (Tao & Zhang 2010). Concentration of this volatile compound was significantly higher in the HHP-treated sample.…”
Section: Volatile Fermentative Compoundsmentioning
confidence: 91%
“…Torulaspora delbrueckii is used for improving aromatic profile in wines (Loira et al 2014) but since its fermentative power range 7-9 % v/v must be used in sequential cultures with Saccharomyces cerevisiae (Ciani & Maccarelli 1998). Metschnikowia pulcherrima develops several enzymatic activities that help enhance varietal aromatic compounds, also by forming fermentative esters (Fernández et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol is an interesting metabolite for wines due to its positive contribution to taste sensations, such as sweetness, softness, silkiness and thickness. Glycerol concentration in wines usually has a 1:10 ratio of the ethanol produced, whilst wine-related yeast varies widely in glycerol production, ranging from 4 g/L to 10 g/L (Loira et al, 2014;Moreno-Arribas & Polo, 2009).…”
Section: Alcoholic Fermentation Of V Labrusca Grape Mustmentioning
confidence: 99%
“…Red wines are the most notable dietary source of resveratrol and usually contain an average resveratrol concentration of 1.9 ± 1.7 mg/L (Fernández-Mar, Mateos, García-Parrilla, Puertas, & Cantos-Villar, 2012), although its concentrations may range from undetectable to 14.3 mg/L (Mark, Nikfardjam, Avar, & Ohmacht, 2005). Differences in the resveratrol concentration in wines depend on grape variety, geographical region, plant stress and oenological practices (Stervbo, Vang, & Bonnesen, 2007).…”
Section: Introductionmentioning
confidence: 99%